Pop culture and the dark side of the American dream : con men, gangsters, drug lords, and zombies - Cantor, Paul A. (Paul Arthur), 1945-2022 (University Press of Kentucky, 2019)
What is the American dream, and why has it proven so elusive for many people? By examining popular culture's portrayal of the dark side of the American dream, this text seeks to answer these questions.